Impacto da covid-19 no sistema auditivo : revisão narrativa - Guerra, Josiane de Souza (2022)
Since the beginning, the pandemic has had major impacts on the global health system. The biggest challenge was regarding the symptoms and consequences caused by the virus, as well as the finding in relation to an effective vaccine or drug. Hearing is essential for all of us, as it develops speech, allowing us to produce sounds and to communicate. The present work is justified due to the large number of people who, after contracting the SARS-CoV-2 virus, called COVID-19, reported hearing problems. It aims to carry out a bibliographic survey in relation to the hearing problems reported by patients who were affected by the COVID-19 virus, as well as to investigate whether the contagion by COVID-19 can be considered a factor for the reduction of hearing acuity, analyzing the main medications used during the COVID-19 pandemic, seeking to understand whether the medications used may have contributed to hearing loss. Its methodology was a narrative review of the literature, of a qualitative nature, and analysis of case reports. At the research level, the results were satisfactory, it can be verified that there is evidence that COVID-19 has harmful effects on people’s hearing and, due to the large number of infected patients throughout this pandemic, hearing changes were evidenced in some patients. From the studies presented in this work, it was possible to conclude that COVID-19 interferes with the auditory system, however, it requires further studies and scientific analysis on the impacts of the virus on the auditory system.